How do mood states change in a multi-stage cycling competition? Comparing high and low performers - Murgia, M.; Forzini, F.; Filho, E.; Di Fronso, S.; Sors, F.; Bertolo, M.; Agostini, T. (The Journal of Sports Medicine and Physical Fitness, 2016)
Our purposes were to investigate: (a) differences in mood states between high and low performers at the beginning and end of the Girobio 2012 cycling race, and in respect to both actual and perceived performance; and (b) whether the participants' mood states predicted actual and perceived performance. Profile of Mood States (POMS) of 72 elite cyclists were assessed the day prior to the first (T0) and last stage (T1). At the end of the race, we created two rankings, one based on the total time spent to complete the race (actual ranking) and one based on the average of self-evaluations provided at the end of each stage (perceived ranking). We compared high and low performers, considering both rankings, using a general measure of mood; i.e. the Total Mood Disturbance. Total Mood Disturbance differed among high and low performers. In particular, high performers' mood disturbance did not differ between T0 and T1, whereas low performing cyclists showed higher levels of mood disturbance at the end of the race. Furthermore, we found that mood disturbance at T0 did not predict either actual or perceived performance. The cyclists' mood states at the beginning of the race are not reliable predictors of performance throughout the race. High performing cyclists maintained a more positive mood profile than their low performing counterparts at the beginning and end of a multi-stage race.